Representation of Ukhuwah Islamiyah Message in the Novel Kambing dan Hujan By Mahfud Ikhwan (Study of Literature Sociology) - Wirayudha Pramana Bhakti; Ulfatunnisa (IQTIDA : Journal of Da'wah and Communication, 2022)
Da'wah media is important as a message transmission that facilitates the delivery of da'wah messages in the form of good values. One of the print media that is used as a propaganda medium is novel. The novel Kambing dan Hujan written by Mahfud Ikhwan carries the theme of socio-religious life which is full of da'wah messages. The novel Kambing dan Hujan has two major premises in its story, the romance and upheaval of two people who in the story represent the horizontal conflict of two major Islamic organizational entities in Indonesia, Nahdlatul Ulama (NU) and Muhammadiyah. In addition to representing the conflict between the two largest Islamic organizations in Indonesia, the novel also represents ukhuwah islamiyah as a way out of the conflict. Through the study of the sociology of literature, it will examine and describe the representation of the message of brotherhood Islamiyah in the novel. This research is a type of library research, the method in this research is qualitative research. The results of the discussion show that in the novel there are three representations of the message of ukhuwah Islamiyah: 1) Ukhuwwah fi din Al-Islam, a brotherhood among Muslims. 2) Ukhuwwah fi Al-'ubudiyyah which is the brotherhood of all creatures in the sense of equality, namely equality in creation and submission to Allah. 3) Ukhuwwah fi Al-wathaniyah wa Nasab which is a brotherhood that is intertwined in descent and also of the same nationality.